2014
DOI: 10.3126/jpn.v4i8.11500
|View full text |Cite
|
Sign up to set email alerts
|

A clinicopathological study of dysfunctional uterine bleeding

Abstract: Background: Dysfunctional uterine bleeding is a form of abnormal uterine bleeding when there is absence of organic disease of the genital tract. The objective of this study was to find out the clinical and pathological aspect of women presenting with dysfunctional uterine bleeding.Materials and Methods: A descriptive study was conducted over a period of one year from April 14th 2010 to April 13th 2011 in the Department of Obstetrics and Gynaecology and Department of Pathology, Tribhuvan University Teaching Hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 3 publications
(1 reference statement)
1
5
0
Order By: Relevance
“…However, iatrogenic DUB is due to drugs, exogenous hormone administration, intrauterine contraceptive devices. 5 AUB is a common problem imposing a significant impact on quality of life and financial burden in women of reproductive age group and it occurs in about 9-14% of women. About one third of hysterectomies are carried out for menstrual disorder alone and thyroid dysfunction is one of the important cause.…”
Section: Introductionmentioning
confidence: 99%
“…However, iatrogenic DUB is due to drugs, exogenous hormone administration, intrauterine contraceptive devices. 5 AUB is a common problem imposing a significant impact on quality of life and financial burden in women of reproductive age group and it occurs in about 9-14% of women. About one third of hysterectomies are carried out for menstrual disorder alone and thyroid dysfunction is one of the important cause.…”
Section: Introductionmentioning
confidence: 99%
“…We found atrophic endometrium in 3.26% of cases whereas Nayak et al, in 2.5% of cases 7 , Katuwal et al, in 68% of cases 24 . Atrophic endometrium was observed in cases of more than 50 years of age.…”
Section: Discussionmentioning
confidence: 46%
“…8 Nepal et al also concluded that the most common age group of women with AUB was 40-44y. 9 In Gubbal et al study, 39.4% of cases belong to 41-50y and 33.5% to 31-40y. 10 In Rizwi et al, Muzaffar et al, and Jairajpur et al study, the majority of cases belonged to the fifth decade.…”
Section: Discussionmentioning
confidence: 88%